1973
DOI: 10.1111/j.1471-4159.1973.tb00097.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of N‐acetylaspartate amidohydrolase (Aminoacylase II) in the developing rat1

Abstract: Of The amino acids and derivatives, N‐acetyl‐L‐aspartic acid is present in a uniquely high level (5–6 μmol/g) in the brain of mammals after myelination has occurred. Much lower levels (0·06–0·17 μmol/g) are found prior to this stage of brain development (Tallan, 1957). In non‐nervous tissues, on the other hand, only trace amounts of this acetyl amino acid are present (Tallan, Moore and Stein, 1956). N‐acetyl aspartic acid serves as an excellent source of acetyl groups for lipogenesis in the developing rat brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…Another used global ischemia to induce depolarization and found that NAA increased 5e10 times in the perfusate [25]. The calculated half-life of released NAA is very short being of the order of seconds to minutes [26], and as a consequence the neuron to ECF NAA gradient in brain would be expected to be high. Evidence of this has been obtained based on rat brain microdialysis studies, where the normal steady-state concentration of NAA in GM ECF was found to be very low (about 20 mM) at any given moment [27].…”
Section: Naa Metabolism In Normal Brainmentioning
confidence: 99%
“…Another used global ischemia to induce depolarization and found that NAA increased 5e10 times in the perfusate [25]. The calculated half-life of released NAA is very short being of the order of seconds to minutes [26], and as a consequence the neuron to ECF NAA gradient in brain would be expected to be high. Evidence of this has been obtained based on rat brain microdialysis studies, where the normal steady-state concentration of NAA in GM ECF was found to be very low (about 20 mM) at any given moment [27].…”
Section: Naa Metabolism In Normal Brainmentioning
confidence: 99%
“…Seven amino acids (Arg63, Asn70, Arg71, Tyr164, Arg168, Glu178 and Tyr288) form the catalytic site of the enzyme, in which Arg168 and Tyr288 stabilize NAA binding to the active site (Bitto et al, 2007;Le Coq et al, 2008). ASPA is present in various tissues, but predominantly in the kidney and white matter of the brain, specifically in oligodendrocytes (Baslow et al, 1999;Birnbaum et al, 1952;D'Adamo et al, 1973;Madhavarao et al, 2004). Genetic deficiency of ASPA follows an autosomal-recessive trait of inheritance and is the cause of Canavan disease (CD) (Kaul et al, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Although NAA is of neuronal origin, its primary site of catabolism is in oligodendrocytes where it is hydrolyzed by the enzyme aspartoacylase (ASPA) to generate free acetate and aspartate (9). NAA-derived acetate needs to be converted to acetyl-coenzyme A (acetyl-CoA) via the cytosolic/nuclear enzyme acetyl-CoA synthetase 1 (AceCS1) for lipid biosynthesis and histone/protein acetylation (10) or mitochondrial acetyl-CoA synthetase 2 for use in the Krebs cycle (11).…”
mentioning
confidence: 99%